THE EFFECT OF RESIN CONTENT AND PRESS TIME ON PROPERTIES OF PARTICLEBOARD PRODUCTION FROM SOUTHERN LIGNOCELLULOSIC MATERIALS IN IRAN - Amir Nourbakhsh; Abolfazl Kargarfard (تحقیقات علوم چوب و کاغذ ایران, 2005)
In this study the effect of resin content and press time of particleboard from Date palm residues, Eucalyptus camaldulensis, Tamarix residues and prosopis (Mesquite) producted were investigated in southern of Iran.Variable factors as resin content (9, 10 and 11 percent) and press time (5, 6 and 7 minutes) and total of 27 boards were fabricated. Other factors such as type of resin (UF), hardener content (2 percent) type of hardener (NH4Cl) press closing time (4.5 mm/sec.), board density (0.7 gr/cm3) press pressure (30 kg/cm2) and press temperature (160 °C)were held constant.All boards were tested according to DIN-68763 standard. The factorial experimental design at completely random test was used. The results of this study could be summarized as follows:Increasing the resin content from 9 to 11 percent, MOE and IE and decreased thickness swelling after two and 24 hours immersion in water. The results revealed that the polymerization of resin and wood is better at 11 percentresincontentand6 minutes of press time.